Character education learning for high school students with a Contextual Teaching Learning (CTL) Approach in Civics Subjects in West Seram District - Rukua, La Kasman; Siregar, Eveline; Wirasti, R A Murti Kusuma (Journal of Education Research and Evaluation, 2021)
This research is development (R & D). In this research purpose to develop a character education learning module contextual teaching and learning (CTL) approach of PKn subject. This research was conducted at SMA Negeri 7 Kabupaten Seram Bagian Barat. This research method refers to the development model of Derek Rowntree and Dick &Carry. The development procedure through three stages, the first stage uses Dick & Carry model until the seventh step is selecting and developing. In the second and third stages using Derek Rowntree model. Review process through reviews of media expert and instructional design expert and reviews of media and language experts. To the target, a one-to-one test was conducted, small group test and field test. Evaluation is carried out until summative evaluation with calculations N-Gain Score to measure the level of effectiveness. The result of effectiveness state that the student character learning module in PKn subject is effective in used.